2019
DOI: 10.1038/sdata.2019.37
|View full text |Cite
|
Sign up to set email alerts
|

Circumpolar permafrost maps and geohazard indices for near-future infrastructure risk assessments

Abstract: Ongoing climate change is causing fundamental changes in the Arctic, some of which can be hazardous to nature and human activity. In the context of Earth surface systems, warming climate may lead to rising ground temperatures and thaw of permafrost. This Data Descriptor presents circumpolar permafrost maps and geohazard indices depicting zones of varying potential for development of hazards related to near-surface permafrost degradation, such as ground subsidence. Statistical models were used to predict ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 111 publications
(128 reference statements)
0
34
2
Order By: Relevance
“…We found that the performance of ERA5L is intermediate between the two maps (Table 2). Whereas Karjalainen et al (2019b) found that the predictive accuracy of their statistical model was similar between permafrost and non-permafrost regions, our results show ERA5L and TTOP soil temperature agree less with observations in permafrost regions than in nonpermafrost regions (Table 2; Fig. 3).…”
Section: Soil Temperaturecontrasting
confidence: 81%
See 1 more Smart Citation
“…We found that the performance of ERA5L is intermediate between the two maps (Table 2). Whereas Karjalainen et al (2019b) found that the predictive accuracy of their statistical model was similar between permafrost and non-permafrost regions, our results show ERA5L and TTOP soil temperature agree less with observations in permafrost regions than in nonpermafrost regions (Table 2; Fig. 3).…”
Section: Soil Temperaturecontrasting
confidence: 81%
“…It incorporates new soil and snow hydrology (Balsamo et al, 2009;Dutra et al, 2010), revised soil thermal conductivity (Peters-Lidard et al, 1998), vegetation seasonality (Boussetta et al, 2013), and bare soil evaporation (Albergel et al, 2012). These improvements are expected to make ERA5L more accurate for many land applications; with a spatial resolution of 0.1 • , ERA5L is the first global reanalysis product at an intermediate spatial scale between Earth system land surface models (e.g., Melton et al, 2019;Chadburn et al, 2015) and statisticaland/or remote-sensing-based permafrost products (e.g., Obu et al, 2019;Karjalainen et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…ERA5L is currently available for 2001-2018, and it will eventually be extended back to 1950 and updated to the present time with little delay. (Karjalainen et al, 2019a). While ERA5L, TTOP and CP maps represent permafrost distribution with binary information (i.e.…”
Section: Era5 and Era5-landmentioning
confidence: 99%
“…Given the lack of high-resolution circum-Arctic model projections of permafrost thaw and subsidence, recent risk assessment studies of infrastructure failure have used statistical approaches and suggested that fundamental engineering structures in the Arctic are at risk by mid-century (Hjort et al, 2018;Karjalainen et al, 2019). Such statistical approaches allow accounting for various sources of local-scale information such as ground ice content, sediment type, or slope gradient at comparatively low computational costs.…”
Section: Introductionmentioning
confidence: 99%